2019
DOI: 10.1177/0031512519829624
|View full text |Cite
|
Sign up to set email alerts
|

Visual Scanning Behavior and Attention Strategies for Shooting Among Expert Versus Collegiate Korean Archers

Abstract: This study analyzed differences in visual scanning behavior and resistance to distractions between Olympic and collegiate archers. The experiment required the participants to watch a test film comprising six stages corresponding to the phases of an archery performance. The recording emulated the archer's point of view. During initial phases of shooting, Olympic archers demonstrated more frequent and longer fixations than did their collegiate counterparts, whereas during the later phases of shooting, the groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…When focusing on body movement, expert golfers base their motor control on proprioceptive and vestibular signals rather than visual inputs, which they instead integrate in the swing motor programming. Similarly, Kim et al (2019) [ 26 ] analysed the differences in shooting behaviour of Olympic vs. collegiate archers. Olympic athletes were able to exclude any type of confounding factors during the shot and visual parameters such as fixation or eye movements were optimised as compared to collegiate archers.…”
Section: Stereopsis and Sportsmentioning
confidence: 99%
See 1 more Smart Citation
“…When focusing on body movement, expert golfers base their motor control on proprioceptive and vestibular signals rather than visual inputs, which they instead integrate in the swing motor programming. Similarly, Kim et al (2019) [ 26 ] analysed the differences in shooting behaviour of Olympic vs. collegiate archers. Olympic athletes were able to exclude any type of confounding factors during the shot and visual parameters such as fixation or eye movements were optimised as compared to collegiate archers.…”
Section: Stereopsis and Sportsmentioning
confidence: 99%
“…However, a specific vision training method has been proposed to improve putting or shooting skills in both golf and archery. Overall, it appears that in putting/shooting sport actions, non-professional athletes base their gesture programming mainly on stereoptic inputs, which, however, should be—with experience—progressively integrated by attentional, proprioceptive, and vestibular inputs [ 22 , 26 ].…”
Section: Stereopsis and Sportsmentioning
confidence: 99%
“…The roles of attentional modulation across perceptual inputs and executive control of attention have been discussed in different sports [for a review, see Memmert ( 2009 )]. In shooting and archery sports, the roles of arousal, vigilance, orienting, and conflict control have been stressed (Bertollo et al, 2012 ; Kim et al, 2019 ; Lu et al, 2021 ). However, the fact that many athletes of shooting and archery are actually shortsighted reminds us that there may also be some other attention ability that contributes to the success in shooting and archery.…”
Section: Introductionmentioning
confidence: 99%
“…Di Russo et al ( 2003 ) reported shorter saccadic latency, and more stable fixation in the presence of distractors in elite shooters. Kim et al ( 2019 ) compared the scanning strategy of archers of the Korean national team with collegiate archers in a procedure with emulating the actual archery situation. In the earlier phase of shooting fixation, duration of the elite archers was longer, and the number of saccades was reduced in comparison to the less experienced archers.…”
Section: Introductionmentioning
confidence: 99%